In the Modern Era of CT, Do Blunt Trauma Patients with Markers for Blunt Bowel or Mesenteric Injury Still Require Exploratory Laparotomy?. Issue 7 (July 2017) - Young, Katelyn; Benson, Melina; Higgins, Andrew; Dove, James; Hunsinger, Marie; Shabahang, Mohsen; Blansfield, Joseph; Torres, Denise; Widom, Kenneth; Wild, Jeffrey
After blunt trauma, certain CT markers, such as free intraperitoneal air, strongly suggest bowel perforation, whereas other markers, including free intraperitoneal fluid without solid organ injury, may be merely suspicious for acute injury. The present study aims to delineate the safety of non-operative management for markers of blunt bowel or mesenteric injury (BBMI) that are suspicious for significant bowel injury after blunt trauma. This was a retrospective review of adult blunt trauma patients with abdominopelvic CT scans on admission to a Level I trauma center between 2012 and 2014. Patients with CT evidence of acute BBMI without solid organ injury were included. The CT markers for BBMI included free intraperitoneal fluid, bowel hematoma, bowel wall thickening, mesenteric edema, hematoma and stranding. Two thousand blunt trauma cases were reviewed, and 94 patients (4.7%) met inclusion criteria. The average Injury Severity Score was 13.6 ± 10.1 and the median hospital stay was four days. The most common finding was free fluid (74 patients, 78.7%). The majority of patients (92, 97.9%) remained asymptomatic or clinically improved without abdominal surgery. After a change in abdominal examination, two patients (2.1%) underwent laparotomy with bowel perforation found in only one patient. Thus, 93 patients did not have a surgically significant injury, indicating that these markers demonstrate 1.1 per cent positive predictive value for bowel perforation. The presence of these markers after blunt trauma does not mandate laparotomy, though it should prompt thorough and continued vigilance toward the abdomen.